Zu hybriden Kommunikationsformen im Online-Diskurs von NGOs - Marcelina Kałasznik (Linguistische Treffen in Wrocław)
The rapid development of the internet and its ubiquity have had a huge impact on forms of communication and text types. The emergence of new and the modification of traditional forms of communication are not new phenomena. However, the changes in this area are so diverse that the topic has been taken up in many linguistic publications. One example of this is the comprehensive monograph “Stille, Bilder und Wörter. Die Bedeutungskonstitution in der digitalen Multimodalität. Mit einer Einführung von Gerda Haßler und einem Vorwort von Carla Marello” by Silvia Verdiani, which was published by Frank & Timme in 2023 and is discussed in the following article. In her study, the author aims to grasp the nature of language-image conglomerates, to characterize their typical features and to point out mechanisms of how the meaning of digital texts emerges from the interplay of their various elements. Verdiani develops an integrative model for the interpretation of digital texts against the background of a detailed theoretical introduction in which she addresses concepts from cognitive linguistics, pragmalinguistics and text linguistics. The corpus with which the author works consists of digital texts from non-governmental and non-profit organizations that represent the online discourse on migration between 2015 and 2019. In her analysis, the author draws attention to the process of hybridization as well as to the phenomena of intertextuality and deixis, which play a special role in the constitution of meaning in digital texts. In this sense, the monograph is a comprehensive account of the production, organization and reception of digital texts.